Analysis of Caring Services for Pregnant Women by Tuha Peut Against the Prevention of Kek Pregnant Women in Suak Bilie Village - Mariyani; Teungku Nih Farisni (Sean Institute, 2022)
In Aceh, the prevalence of KEK risk for pregnant women aged 15-49 who are pregnant is 20%, while nationally, the prevalence of KEK risk for WUS is 21%. In Nagan Raya district itself in 2020 pregnant women with chronic energy deficiency conditions (KEK) are 5.2% with 158 cases and sub-districts are 12.5% with 21 cases. Meanwhile, in 2021, KEK pregnant women are 4.6% with cases 140 and glasses, namely 13.2% with a total of 22 cases. Qualitative method with descriptive approach by collecting through interviews and questionnaires. There are 21 responders from the village of Suak Bilie, all of whom are pregnant women and tuha peut. In the village of Suak Bilie, as many as 17% of pregnant women suffer from chronic energy deficiency (KEK), which is indicated by an upper arm circumference of less than 23.5 cm. and as many as 83% of pregnant women who did not experience KEK which was marked by an upper arm circumference of 23.5 cm. The Gampong Qanun clearly stipulates that tuha peut is one of the gampong apparatuses who have duties and responsibilities in implementing prevention and control of KEK in pregnant women in Suak Bilie Village. Services for KEK in the village of Suak Bilie have been regulated in Qanun Number 03 of 2022 concerning the handling and prevention of KEK for pregnant women. Factors that occur in pregnant women in Suak Bilie Village, Nagan Raya Regency, are factors of age, knowledge or education, food intake, behavior, family income and parity factors of pregnant women.